2002
DOI: 10.1016/s0022-5347(05)65411-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Testicular Biopsy in the Modern Management of Male Infertility

Abstract: In the vast majority of patients obstructive azoospermia may be distinguished clinically from nonobstructive azoospermia with a thorough analysis of diagnostic parameters. Based on this result, we believe that the isolated diagnostic testicular biopsy is rarely if ever indicated. Men with FSH 7.6 mIU/ml. or greater, or testicular long axis 4.6 cm. or less may be considered to have nonobstructive azoospermia and counseled accordingly. These men are best treated with therapeutic testicular biopsy and sperm extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(91 citation statements)
references
References 12 publications
10
70
0
2
Order By: Relevance
“…Testicular size was determined by measuring the longitudinal dimension of each testicle with a ruler. Schoor et al found that a longitudinal testicular length of greater than 4.6 cm has a 72% sensitivity and 78% specificity of diagnosing OA [5] . We used a similar criterion to exclude patients from the study if they had a documented longitudinal length of greater than 4.6 cm which would suggest OA.…”
Section: Methodsmentioning
confidence: 99%
“…Testicular size was determined by measuring the longitudinal dimension of each testicle with a ruler. Schoor et al found that a longitudinal testicular length of greater than 4.6 cm has a 72% sensitivity and 78% specificity of diagnosing OA [5] . We used a similar criterion to exclude patients from the study if they had a documented longitudinal length of greater than 4.6 cm which would suggest OA.…”
Section: Methodsmentioning
confidence: 99%
“…5,9 Relevant historical factors in the evaluation of azoospermia are listed in Table 1 12 These findings are reflected in current guidelines on the evaluation of azoospermia and have greatly reduced the need for testicular biopsy in the evaluation of azoospermia. 5,9 The purpose of this case report is to discuss a diagnostically challenging presentation of azoospermia in the context of current recommendations and to propose a situation-specific treatment algorithm to aid in the management of azoospermia and varicocele.…”
Section: Cuaj -Residents' Room Masterson Et Al Case: Azoospermia Withmentioning
confidence: 99%
“…According to Schoor et al (2), a testis biopsy could promote scars that make the following biopsy procedures more difficult. Sousa et al (4) consider testicular biopsy the best method for sperm retrieval in non-obstructive azoospermic patients, considering that in testicular atrophy cases percutaneous sperm aspiration was not able to provide enough material for ICSI.…”
Section: Commentsmentioning
confidence: 99%
“…Considering that spermatogenesis recovery after a biopsy procedure is slow, it is essential to avoid unnecessary biopsies (16). A maximum of 3 procedures must be performed and, whenever possible, they should be associated with cryopreservation techniques (4,2). This care reduces the risk of complications without impairing fertilization and pregnancy rates (16).…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation